Фарфор: [стихи] / Вероника Долина ; [рисунки А. Смирнова] - Долина Вероника Аркадьевна (ЭКСМО, 2010)
Экземпляры: АБ (20110622) / Инвентарный номер: 39708zzzzz / Цена: 234.33 / Сис.шифр: 84(2) / Авт.знак: Д 64 / ГРНТИ: 17.82.10 / ББК: 84(2=Рус)